AI Algorithm Based Jacket Ejection For Automatic Security System in Water Bodies (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
It is tedious process and takes time to detect the person on water by usual ways like with the help of rescue teamand divers. To overcome this, we have introduced this work with a life camera and edge detection algorithm for detectingdrowning person. When raspberry PI identifies the drowning person, it will initialize the servo motor which will eject the lifejacket automatically. The greatest advantage of this proposed work is that this whole system is made into a boat shaped botand is completely automatic process. Python language is preferred for AI algorithm and to specify edge detection process.